Jurema e umbanda nas vozes de Mãe Rita Preta e Mãe Marinalva: narrativas do pioneirismo feminino nos cultos afro-indígenas da Paraíba - Medeiros, Maria Gomes de (2022)
The present work involves research on oral narratives (depositions, life stories) and autobiographical accounts of Mãe Rita Preta and Mãe Marinalva, former juremeiras/umbandistas from the city of João Pessoa and Santa Rita. With regard to the memories of Mãe Rita Preta, we will focus on the ethnographic work undertaken by Valdir Lima, present in the book Cultos Afro-Paraibanos: Jurema, Umbanda e Candomblé (2020), the result of his master's thesis in science of religions. We will also feature the analysis of the documentary Santa Rita Preta (2007), organized by the ONG Encumbe, directed by Cleyton Ferrer and research work by Valdir Lima. Mãe Marinalva's memories are based on the book Umbanda: Missão do bem: minha história, minha vida (2013), narrated by Mãe Marinalva and transcribed and organized by Dr. Giovanni Boaes. We are interested in understanding, from the experience of these women, who were precursors of the cult of Umbanda and Jurema in the state of Paraíba and also essential political subjects for the struggle for the freedom of Afro cults in the sixties, such as the collective narratives of terreiros of the Jurema decade and Umbanda (re)construct the mythical memory (SODRÉ, 2018) of populations in Afro-Indigenous diaspora contexts. We will stick to the concepts of spiral time (MARTINS), so that they understand this narratives, according to the ethical and political imperatives firm in the cross of temporalities typical of diaspora voices. We use concepts from cultural, feminist and decolonial studies, authors and authors who have focused on topics such as “coloniality” and “decoloniality”, “diaspora”, “epistemicide”, “social and cognitive justice” (GONZALEZ, 2008; COLLINS, 2019; FANON, 1968; QUIJANO, 2005; SOUSA SANTOS, 2019).